Working from home and Covid-19: the chances and risks for gender gaps - Arntz, Melanie; Ben Yahmed, Sarra; Berlingieri, Francesco (ZEW-Kurzexpertise, 2020)
As the Covid-19 pandemic causes an all-time high share of people to work from home, this disruptive event is likely to have a long-lasting effect on work arrangements. Given existing research on the effects of working from home (WfH) on hours worked and wages, an increased availability of WfH may provide a chance for women to catch up with their male counterparts. Yet, the need to simultaneously care for children during the Covid-19 lockdown may also revive traditional gender roles, potentially counteracting such gains. This expert brief discusses the likely effects of the Covid-19 pandemic on gender gaps in light of recent empirical findings and novel statistics on the heterogeneous structure of work arrangements among couples.